Enhancing Science Education in the K-12 Program: Exploring theImpact of Differentiated Instruction Strategies (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aimed to determine the level of academic achievement of the grade 7 Biology class during the second period using the differentiated instruction for the experimental group. Pre-test post-test experimental design was utilized in this study. The research subjects-respondents of this study were the grade 7 students of one Secondary Education Institutions in the Philippines . The data in this study were obtained using the questionnaires. Frequency, mean, t-test, and f-test were the statistical tools used in this study. A 0.05 level of significance was used to determine whether the hypothesis set in the study will be rejected or accepted. The statistical computations were done using the Statistical Package of Social Science (SPSS). The research findings revealed that the level of achievement of the grade 7 students in Biology during the pre-test and post-test and when take as a whole were very low. However, when grouped according to the experimental and control group, the pre-test post-test of the experimental group ranges from very low to very high, while the control group ranges from very low to average. Findings, also revealed that there is a significant difference in the mean gains in the pre-test and post-test of the experimental and control group. The study also revealed that there is no significant difference between the levels of achievement of the subjectrespondents when grouped according to the identified variables in their profiles.